Magnetresonanzneurographie bei diabetogener Polyneuropathie - Jende, Johann; Bendszus, Martin (Der Diabetologe, 2019)
BackgroundClinical studies on the course and potential causes of diabetic polyneuropathy are restricted to electrophysiological examinations and biopsies of distal nerves, since access to proximal nerves such as the proximal sciatic nerve is limited for both electrophysiological examinations and biopsies in clinical routine. High resolution magnetic resonance neurography (MRN) is a new tool that allows assessment of both proximal and distal nerves at the fascicular level.Objectives, materials and methodsThe objective of this article is to explain how MRN is applied and to summarize the results of recent studies on MRN in patients with diabetic polyneuropathy.ResultsIn recent studies on MRN in patients with diabetic polyneuropathy it was shown that, in spite of the evolution of clinical symptoms, the predominant site of nerve damage is located at the thigh level. Furthermore, it was found that patterns of nerve damage differ between people with type 1 and type 2 diabetes and that different types of nerve lesions can be attributed to different risk factors: while the predominant type of nerve lesions in type 1 diabetes is associated with elevated HbA1c (glycohemoglobin type A1c) levels, the predominant type of nerve lesions in type 2 diabetes is associated with low HDL (high density lipoprotein) cholesterol and elevated triglyceride values.ConclusionsThe results of MRN studies in patients with diabetes indicate that in type 2 diabetes dyslipidemia is an important contributor to diabetic neuropathy in addition to hyperglycemia. These results may serve to explain the poor effect of glycemic control on the progression of diabetic polyneuropathy in patients with type 2 diabetes in several interventional studies.